Hydrogel-Based Strategies for Intervertebral Disc Regeneration: Advances, Challenges and Clinical Prospects - Shivam U. Desai; Sai Sadhananth Srinivasan; Sangamesh Gurappa Kumbar; Isaac L. Moss (Gels, 2024)
Millions of people worldwide suffer from low back pain and disability associated with intervertebral disc (IVD) degeneration. IVD degeneration is highly correlated with aging, as the nucleus pulposus (NP) dehydrates and the annulus fibrosus (AF) fissures form, which often results in intervertebral disc herniation or disc space collapse and related clinical symptoms. Currently available options for treating intervertebral disc degeneration are symptoms control with therapy modalities, and/or medication, and/or surgical resection of the IVD with or without spinal fusion. As such, there is an urgent clinical demand for more effective disease-modifying treatments for this ubiquitous disorder, rather than the current paradigms focused only on symptom control. Hydrogels are unique biomaterials that have a variety of distinctive qualities, including (but not limited to) biocompatibility, highly adjustable mechanical characteristics, and most importantly, the capacity to absorb and retain water in a manner like that of native human nucleus pulposus tissue. In recent years, various hydrogels have been investigated in vitro and in vivo for the repair of intervertebral discs, some of which are ready for clinical testing. In this review, we summarize the latest findings and developments in the application of hydrogel technology for the repair and regeneration of intervertebral discs.